Peramalan Produksi Hidrokarbon Berdasarkan Decline Curve Analysis (DCA) Dengan Metode Levenberg-Marquardt Algorithm (LMA) Pada Sumur HS-0105 Lapangan AG - Hasnawi Hs; Dharma Arung Laby; Abdi Suprayitno; Abdul Gafar Karim; Amiruddin; Luthfiyah Atisa Fadhilah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
Hydrocarbon production forecasting is the process of projecting oil or gas production over a period of time. One commonly used method is production modeling with Decline Curve Analysis (DCA). Many previous studies have used the Trial Error and Chisquare test method in DCA. However, this method has limitations including: long calculation time, modeling is done manually and not automatically, and the fit of the production curve with the data is often inaccurate. To overcome these limitations, a method that is fast, automatic and produces accurate curves with data is needed. One of them is the Levenberg-Marquardt Algorithm (LMA) numerical optimization approach. The Levenberg-Marquardt Algorithm method is an iterative method used to solve nonlinear optimization problems. The Levenberg Marquardt Algorithm method has advantages such as: reliability, fast convergence, and has been widely applied in engineering optimization problems. This study aims to forecast hydrocarbon production, calculate EUR (Estimated Ultimate Recovery) and ERR (estimated remaining reserve) at well HS-0105 AG field. First, a DCA program based on LMA was developed with the MATLAB programming language. After that, the production data is inputted into the LMA program to do production modeling until the optimum curve is obtained. After obtaining the optimum DCA curve, a comparison was made with the curve resulting from trial and error. From the results of DCA curve optimization with LMA, the RMSE (Root Mean Square Error) value = 101,756, R2 (R-squared) value = 0,574, computation time 2-3 seconds in the Levenberg-Marquardt Algorithm (LMA) method while the Trial Error and Chisquare test method RMSE (Root Mean Square Error) value 128.905 R2 (R squared) value = 0.569 and long computation time. From the comparison results, the Levenberg-Marquardt Algorithm (LMA) method is much better than Trial Error and is recommended for use. Based on the Decline Curve Analysis with the Levenberg-Marquardt Algorithm (LMA) method, the EUR (Estimated Ultimate Recovery) value is 14339,525 STB and the ERR (estimated remaining reserve) value is 7693,091 STB at the HS-0105 well in the AG field. With the results of this projection, it is expected that the production of the HS-0105 well in the AG field can be stimulated to withstand the rate of decline in production and even increase.